Conceptual Metaphors and Pragmatics Meanings in Christina Perri’s Songs: “Hurt”, “Blue” & “Mothers” - Herlyna Herlyna; Retno Ramadhina; Aura Pradita (STIBA IEC JAKARTA, 2024)
the writer raises the issue of types of conceptual metaphors and the pragmatic meaning of these metaphorical expressions found in Christina Perri's songs entitled